Educación científica de las niñas, vocaciones científicas e identidades femeninas. Experiencias de estudiantes universitarias - Guevara Ruiseñor, Elsa Susana; Flores Cruz, María Guadalupe (Universidad de Costa Rica, 2018)
In Mexico, as in Latin America, the scientific education of its young constitutes an economic and social imperative especially for the female population that is underrepresented in their science and technology systems. Studies on gender and science have provided enough evidence about the obstacles that represent gender systems to promote the scientific vocations in girls and young women, as well as the importance of the school and the family for reproduce or transform these patterns. This research was proposed as a goal know the way in which operated on the systems of gender in the scientific education of women students during her childhood, its impact on the construction of scientific vocations and her interest in research. We used as a methodological strategy the qualitative interview to depth, these interviews were applied to eight women students for psychology and biology of the UNAM. The results showed that the biology students lived a socialization of less traditional gender in the family and at school, and a scientific education in childhood that contributed to create scientific vocations in them, to promote her interest by university career and devote herself to the research. Such findings identify the important role that complies non-traditional gender socialization to facilitate the scientific education of girls and young women, but also the importance of scientific education of girls for to break traditional female models and choose the scientific career.